Monitoring Korosi Discharge Conveyor H pada Tambang Batubara PT XYZ di Kabupaten Banjar Provinsi Kalimantan Selatan - Dzaky Fajri Saifulloh; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyor is a tool used to move material, usually to move material from one place to another. The conveyor structure has the main constituent material, namely carbon steel which is prone to corrosion so that the steel will experience damage which can reduce the service life of the conveyor structure caused by environmental factors. Therefore, it is necessary to control corrosion in order to slow down the rate of corrosion so as to extend the life of the conveyor. The purpose of this study is to determine the type of corrosion, corrosion handling, corrosion rate and remaining service life (RSL) on the conveyor structure. The methodology used in this study is the measurement of the thickness reduction of the conveyor structure. Actual thickness measurement using Ultrasonic Thickness Gauge TT 130, carried out on a conveyor with a length of 96 meters divided into 3 segments and consisting of 25 test points. in 2016-2020 the research locations had an average rainfall of 211.105 mm/year, an air temperature of 25.75°C, and a relative humidity of 81.75%. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method used is coating with a three layer system with primary coating using seaguard 5000 then intermediate coating using sherglass FF and top coating using aliphatic acrylic modified polyurethane. The corrosion rate ranges from 0.1833 to 0.32 mm/year which is classified into the good category referring to the table of relative corrosion resistance of steel. The design life of the conveyor structure is 15 years and the service life is 6 years. The remaining service life obtained from the calculation results is around 8.19 – 12.94 years, as many as 13 of the 25 test points or 48% of the test points cannot reach the design life. Abstrak. Conveyor ialah alat yang digunakan untuk memindahkan material dari satu tempat ke tempat lainnya. Struktur conveyor memiliki material penyusun utama yaitu baja karbon yang rentan mengalami korosi sehingga baja akan mengalami pengurangan ketebalan yang dapat mengurangi umur pakai dari struktur conveyor tersebut disebabkan oleh faktor lingkungan. Oleh sebab itu diperlukan pengendalian korosi agar dapat memperlambat laju korosi. Tujuan dari penelitian ini untuk mengetahui jenis korosi, penanganan korosi, mengetahui laju korosi (Corrosion rate) dan remaining service life (RSL) struktur conveyor. Metodologi yang digunakan pada penelitian ini adalah pengukuran pengurangan ketebalan struktur conveyor. Pengukuran tebal aktual menggunakan Ultrasonic Thicness Gauge TT 130, dilakukan pada conveyor dengan panjang 96 meter dibagi menjadi 3 segmen dan terdiri dari 25 test point. Pada tahun 2016-2020 lokasi penelitian memiliki curah hujan rata-rata 211,105 mm/tahun, temperatur udara sebesar 25,75°C, dan kelembapan relatif sebesar 81,75 %. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode pengendalian korosi yang dilakukan adalah coating dengan sistem three layer dengan primer coating menggunakan seaguard 5000 lalu intermediate coating menggunakan sherglass FF dan top coating menggunakan aliphatic acrylic modified polyurethane. Corrosion rate berkisar 0,1833 hingga 0,32 mm/tahun yang terklasifikasikan ke dalam kategori good mengacu pada tabel ketahanan korosi relatif baja. Umur desain struktur conveyor 15 tahun dan umur pakai 6 tahun. Remaining service life yang didapatkan dari hasil perhitungan 8,19 – 12,94 tahun, sebanyak 13 dari 25 test point atau 48% test point diprediksi tidak dapat mencapai umur desainnya.